The Lab, Land, and Longing: Discursive Constructions of Australian Identities in ‘Future’ Food Consumption - Errmann, Amy; Conroy, Denise M; Young, Jennifer (SAGE Publications, 2023)
Food consumption is being reconfigured as a consequence of consumers’ ethical concerns. While preferences and tastes may be influenced by broad ethical positions, constructions of social identity also reflect shifts in food consumption. Important tools within this nexus are ‘future foods’, produced through novel technologies such as artificial intelligence or genetic editing, supporting consumers in the construction of identity markers. Through 24 (n = 121) focus groups in rural and urban Australia, we explore to what extent future foods contribute to alleviate tensions between broader ethical principles and consumer identities. We argue that the collective discourse around future foods has the potential to shift the culture of food ethics in the future, enabled through three moral identity markers. Specifically, identities of citizen-consumption that view ethics as ‘eating for change’; nationalism as a form of patriotic morality that encourages the consumption of national brands and protectionism; and nostalgic knowledge and historical identities of the past to reconfigure ethical ideals for the future. These discursive identity constructions shed light on how consumers may redefine food ethics in the future, legitimising citizenship through demonstrating virtue, patriotism as loyalty to social groups, and nostalgic capturing of history to ‘ethicise’ the future.
Keywords: 35 Commerce, Management, Tourism and Services; 4410 Sociology; 44 Human Society; 1505 Marketing; 1608 Sociology; 2002 Cultural Studies; Sociology; 3506 Marketing; 4410 Sociology